ANALISIS ALIRAN PADA BUCKET TURBIN PELTON 1 KW DENGAN VARIASI SPEAR NOZZLE MENGGUNAKAN METODE CFD - Darmawan, Steven; Sutanto, Hadi; De Fretes, Anthon; Octaviani, Sandra; Tanujaya, Harto; Rosehan, Rosehan; Marcellio, Ricco (POROS, 2023)
Pelton turbine have been used for harvesting renewable energy by extracting kineticenergy of water into mechanical energy for more than 100 years. This characteristic makes thissystem remains potential to achieve Goals #12 SDGs. During the operation, the performance ofPelton Turbine is affected by several parameters: hydraulic power, water flow rate, bucketdesign, and nozzle. Among others, nozzle design is the most challenging since this part isresponsible to drive the water direction strike the buckets, converting impulse. The performanceof existing 1 kW Pelton Turbine equipped with 15mm Spear Nozzle is believed can be improvedby varying the nozzle diameter by using low-cost CFD simulation procedure. Ansys Fluent fromAnsys Student 2021 R1 is used in this research. Represented by two-buckets facing spear nozzle,three dimensional CFD simulation is conducted. The nozzle diameter is varied to 15 mm, 14 mm,and 13 mm from two configurations. The first and second configuration is done with water flowrate 3,3 kg/s and 1,3 kg/s respectively. The results show that 15 mm nozzle diameter can producehigher power as high as 594,08 Watt with the first configuration. Even though at the secondconfiguration this 15mm nozzle diameter did not produce the highest power, other parameterssuch as splashing water and erosion effect still show that the 15mm nozzle diameter performedbetter than others. This simulation results also consistent with experimental results whichperformed by using first configuration and 15mm nozzle diameter. The results also show that thesistem performance is much higher at higher water flow rates. Therefore, the development of thesystem can be continued to by using spear nozzle with diameter higher than 15mm.